2010
DOI: 10.1590/s0073-47212010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Biologia reprodutiva de Astyanax henseli (Teleostei, Characidae) do curso superior do Rio dos Sinos, RS, Brasil

Abstract: ABSTRACT. Reproductive biology of Astyanax henseli (Teleostei, Characidae) in the upper Rio dos Sinos, RS, Brazil. This study describes the reproductive biology of a population of Astyanax henseli Melo & Buckup, 2006 from the upper Rio dos Sinos, Caraá, Rio Grande do Sul, Brazil. A total of 336 specimens was analyzed, comprising 169 males, 154 females and 13 individuals of undetermined sex. The reproductive season lasted approximately five months, from August to December, gonadossomatic index (GSI) peaked of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
3
8
0
3
Order By: Relevance
“…As reported in the literature on Astyanax species, there is some variation in the duration of the reproductive period [36]. However, similar to the current findings, most studies on this genus report seasonal reproduction in spring and summer in the Southern Hemisphere (from September to March), with durations ranging from four to six months [19,27,33,38e42].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As reported in the literature on Astyanax species, there is some variation in the duration of the reproductive period [36]. However, similar to the current findings, most studies on this genus report seasonal reproduction in spring and summer in the Southern Hemisphere (from September to March), with durations ranging from four to six months [19,27,33,38e42].…”
Section: Discussionsupporting
confidence: 88%
“…The same reproductive period was observed by Viana et al [19] in a study on A. altiparanae, as well as in studies on A. scabripinnis [24,27,33] and A. paranae [26,35]. The reproductive period of A. henseli was found to be shorter d from August to December [36], and A. bimaculatus exhibited continuous reproductive activity throughout the year, though with reduced gonadal activity from May to July [37].…”
Section: Discussionsupporting
confidence: 73%
“…This reinforces the idea that there is an accumulation of reserves for reproductive activity. Similar results were found for Loricariichthys platymetopon and Rhinelepis aspera (Agostinho et al, 1990;Querol et al, 2002), and also for Characiformes, such as Leporinus copelandii Steindachner, 1875 (Costa et al, 2005), Steindachnerina insculpta (Fernández & Yépez, 1948) (Ribeiro et al, 2007), Astyanax henseli de Melo & Buckup, 2006(Dala-Corte & Azevedo, 2010, among others. According to Svedäng & Wickström (1997), in the case of females, the decrease in HSI during the maturation period is mainly due to the depletion of liver reserves as a result of depletion of glycogen and lipids in hepatocytes, where the synthesis of vitellogenin (Mommsen & Korsgaard, 2008) and transfer to oocytes take place.…”
Section: Discussionsupporting
confidence: 69%
“…Seasonal reproductive cycles may be strongly influenced by biotic factors such as food availability and competition, and abiotic factors such as variations in temperature, photoperiod and rainfall (Dala-Corte & Azevedo, 2010). In tropical regions of Brazil, where the level of the rivers determines the availability of habitat and food, rainfall seems to be the factor that most influences the reproductive cycles of fish (Vazzoler et al, 1997;Agostinho et al, 2004;Bailly et al, 2008;Freitas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found absence of relationship between GSI with RI and HSI (e.g. Lampert et al, 2004;Dala-Corte & Azevedo, 2010). A possible explanation for this result is that food availability may be abundant throughout all the months of year for C. pterostictum in the studied sites.…”
Section: Discussionmentioning
confidence: 59%